Clinical and etiological characterization of a sam-ple of children and adults with dysphagia treated in two healthcare centers in Medellín/Colombia: a retrospective study - Suárez-Escudero, Juan Camilo; Alarcón-Bolívar, Daniela; Correa-Hernández, Sergio Andrés; Bechara-Mestra, María Daniela; Larios-Gómez, Michelle; Toro-Correa, Sara; Gil-Serna, Juan José; Isaza-Arias, John Alejandro (Iatreia, 2022)
Introduction: Dysphagia is a frequent disorder throughout the life cycle, which has different etiolo-gies in relation to its clinical type in oropharyngeal or esophageal.Objective: Clinical and etiological characterization of a sample with dysphagia attended in two health care centers in the city of Medellín (Colombia), showing the etiology and clinical type of dysphagia according to age groups. Methods: Observational, descriptive, and retrospective study, through the review and analysis of and clinical records of patients with a diagnosis of dysphagia, treated between 2012 and 2018 in a university hospital and a speech therapy center in swallowing. Results: Sample of 527 patients. Distributed in tho-se under 18 years 45.4% (239/527); 18 to 59: 20.1% (106/527) and over 60: 34.5% (182/527). Clinical type, etiology, and most frequent health condition in the entire sample: oropharyngeal dysphagia, functional etiology, and neurological diseases. The most frequent conditions causing dysphagia in children under 18 years of age were childhood development disorders; group 18 to 59 years, cancer and, in those over 60 years of age, neurodegenerative processes. Conclusion: Oropharyngeal dysphagia due to functional etiology is common throughout the life cycle, and neurological diseases seem to largely explain its pathophysiology. In older adults it is associated with neurodegenerative disorders, and in those under 60 years of age (including children) the etiology is diverse. Its causes and clinical characteristics must be considered for promotion, diagnosis, treatment, and rehabilitation processes.